Why does diabetes increase atherosclerosis? I don’t know! - Ira J. Goldberg (The Journal of Clinical Investigation, 2004)
There is a wealth of clinical data showing the relationship between diabetes mellitus and atherosclerosis and its clinical complications. To dissect this relationship, investigators have attempted, usually unsuccessfully, to create a small-animal model in which diabetes accelerates vascular lesion development. This effort has often been complicated by development of hyperlipidemia leading to difficulty in differentiating the effects of hyperglycemia from those of lipid abnormalities. A study in the current issue of the JCI provides data on a new mouse model in which atherosclerosis initiation is accelerated in diabetic mice and is reduced by insulin therapy. Moreover, these animals have greater intra-arterial hemorrhage, which might be due to less stable plaques .